Materialities of care encountering health and illness through artefacts and architecture - Buse, Christina; Martin, Daryl; Nettleton, Sarah 1960- (Sociology of health and illness monographs series, 2018)
"Materialities of Care addresses the role of material culture within health and social care encounters, including everyday objects, dress, furniture and architecture. Makes visible the mundane and often unnoticed aspects of material culture and attends to interrelations between materials and care in practice. Examines material practice across a range of clinical and non-clinical spaces including hospitals, hospices, care homes, museums, domestic spaces and community spaces such as shops and tenement stairwells. Addresses fleeting moments of care, as well as choreographed routines that order bodies and materials. Focuses on practice and relations between materials and care as ongoing, emergent and processual International contributions from leading scholars draw attention to methodological approaches for capturing the material and sensory aspects of health and social care encounters"--Provided by publisher.